An Investigation of College Students' Attitudes and Perceptions Regarding Bible Reading Habits: A Descriptive Study - Lumista, Christy; Ganzon, Jhosua Ray C.; Signocan, Manolito Necolas C.; Aznar Jr, Nestor D.; Taja-on, Evan P. (Asian Journal of Philosophy and Religion, 2025)
Bible reading remains a cornerstone of spiritual growth for Christians, yet modern distractions and shifting values have diminished its consistency among young adults who face unique challenges like academic demands and social obligations. Existing research highlights the importance of spiritual practices but often generalizes young adults' habits, leaving a gap in understanding the specific attitudes, perceptions, and factors influencing students' engagement with Scripture. This descriptive study was conducted at San Isidro College with 146 first-year students selected via stratified random sampling. The findings indicate that first-year college students hold a high level of positive attitude toward Bible reading, with an overall mean score of 2.68, valuing its spiritual, emotional, and relational benefits. These results highlight the students' recognition of the spiritual, emotional, and relational benefits of Bible engagement, affirming its significance in their personal and faith development. However, findings also highlight the need for innovative and structured approaches to facilitate engagement and address misconceptions about formal Bible study.